Polarizing plate with phase difference layer and image display device using the same

By introducing a penetrating adhesive layer into the polarized plate, the problem of easy detachment of the liquid crystal composite retardation layer is solved, and the higher stability and service life of the polarized plate is achieved.

JP7657013B2Active Publication Date: 2025-04-04NITTO DENKO CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2018226556
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2018-12-03
Publication Date
2025-04-04
Estimated Expiration
2038-12-03

AI Technical Summary

Technical Problem

In the prior art, the polarized plate of the liquid crystal composite as the retardation layer is prone to detachment problems.

Method used

A polarized plate design including an introduction layer is adopted, wherein the introduction layer is formed at the interface between the liquid crystal composite retardation layer and the adhesive layer by an adhesive penetrating the first adhesive layer, thereby enhancing the adhesion between the retardation layer and the adhesive layer.

Benefits of technology

The detachment phenomenon of the liquid crystal composite retardation layer is effectively suppressed, and the stability and service life of the polarized plate are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657013000002
    Figure 0007657013000002
  • Figure 0007657013000003
    Figure 0007657013000003
  • Figure 0007657013000004
    Figure 0007657013000004
Patent Text Reader

Abstract

To provide a polarizing plate having a retardation layer including an oriented solidified layer of a liquid crystal compound, in which a removal of the oriented solidified layer of the liquid crystal compound is restricted.SOLUTION: A polarizing plate having a retardation layer includes: a polarizing plate including a polarizer and a protective layer at least on one side of the polarizer; and a retardation layer laminated on the polarizing plate interposing a first adhesive layer. The retardation layer is an oriented solidified layer of a liquid crystal compound, and includes a penetration layer formed by penetration of an adhesive agent of the first adhesive layer in a vicinity of a boundary face with the first adhesive layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polarizing plate with a retardation layer and an image display device using the same. [Background technology]

[0002] In recent years, image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (for example, organic EL display devices and inorganic EL display devices), have rapidly become widespread. A polarizing plate and a retardation plate are typically used in image display devices. In practice, a retardation layer-attached polarizing plate in which a polarizing plate and a retardation plate are integrated is widely used (for example, Patent Document 1). Recently, as the demand for thinner image display devices has increased, the demand for thinner retardation layer-attached polarizing plates has also increased. In order to meet such demands, a layer formed by orienting a liquid crystal compound in a predetermined direction and fixing the orientation state has been proposed as a retardation layer. However, there is a problem that such a layer formed of a liquid crystal compound is easily peeled off. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 5745686 Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention has been made to solve the above-mentioned problems in the conventional art, and a main object of the present invention is to provide a polarizing plate with a retardation layer, which has a layer of a liquid crystal compound with a solidified orientation, and in which peeling of the layer of a liquid crystal compound with a solidified orientation is suppressed. [Means for solving the problem]

[0005] The polarizing plate with a retardation layer of the present invention comprises a polarizing plate including a polarizer and a protective layer on at least one side of the polarizer, and a retardation layer laminated on the polarizing plate via a first adhesive layer. The retardation layer is an alignment-solidified layer of a liquid crystal compound, and includes a permeation layer formed by permeation of the adhesive of the first adhesive layer in the vicinity of the interface with the first adhesive layer. In one embodiment, the polarizing plate includes the polarizer and a protective layer arranged on the opposite side of the polarizer to the retardation layer. In another embodiment, the polarizing plate includes the polarizer and protective layers disposed on both sides of the polarizer. In this case, the protective layer disposed on the retardation layer side of the polarizer may include a permeation layer formed by permeation of the adhesive of the first adhesive layer in the vicinity of the interface with the first adhesive layer. In one embodiment, the retardation layer is a single layer of an aligned and solidified liquid crystal compound, the retardation layer has a Re(550) of 100 nm to 190 nm, and the angle between the slow axis of the retardation layer and the absorption axis of the polarizer is 40° to 50°. In another embodiment, the retardation layer has a first liquid crystal compound alignment layer and a second liquid crystal compound alignment layer laminated on the first liquid crystal compound alignment layer via a second adhesive layer; the first liquid crystal compound alignment layer and the second liquid crystal compound alignment layer each include a permeation layer formed by the adhesive of the second adhesive layer permeating near the interface with the second adhesive layer. The first liquid crystal compound alignment layer has a Re(550) of 200 nm to 300 nm, and the angle between the slow axis and the absorption axis of the polarizer is 10° to 20°; the second liquid crystal compound alignment layer has a Re(550) of 100 nm to 190 nm, and the angle between the slow axis and the absorption axis of the polarizer is 70° to 80°. In one embodiment, the adhesive of the first and second adhesive layers each comprises acryloylmorpholine. In one embodiment, the retardation layer-attached polarizing plate further has another retardation layer on the outer side of the retardation layer, and the refractive index characteristics of the another retardation layer satisfy the relationship nz>nx=ny. According to another aspect of the present invention, there is provided an image display device, the image display device including the above-mentioned retardation layer-attached polarizing plate. Effect of the Invention

[0006] According to the present invention, in a polarizing plate with a retardation layer having a solidified alignment layer of a liquid crystal compound, by providing a permeation layer formed by penetration of the adhesive of the adhesive layer near the interface between the alignment layer of the liquid crystal compound and an adjacent adhesive layer, it is possible to realize a polarizing plate with a retardation layer in which peeling of the alignment layer of the liquid crystal compound is suppressed. [Brief description of the drawings]

[0007] [Figure 1] 1 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to another embodiment of the present invention. [Diagram 3] FIG. 11 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to still another embodiment of the present invention. [Figure 4] 2 is a transmission electron microscope (TEM) image showing the state of the interface between the adhesive layer and the retardation layer in the retardation layer-attached polarizing plate of Example 1. [Diagram 5] 1 is a TEM image showing the state of the interface between the adhesive layer and the retardation layer in the retardation layer-attached polarizing plate of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0009] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means ±45°. (6) Oriented solidified layer The term "alignment fixed layer" refers to a layer in which liquid crystal compounds are aligned in a predetermined direction and the alignment state is fixed. The term "alignment fixed layer" is a concept that includes an alignment hardened layer obtained by hardening a liquid crystal monomer as described below. (7) (Meth)acrylic "(Meth)acrylic" refers to acrylic and / or methacrylic.

[0010] A. Overall structure of the polarizing plate with a retardation layer FIG. 1 is a schematic cross-sectional view of a polarizing plate with a retardation layer according to one embodiment of the present invention. The polarizing plate with a retardation layer 100 in the illustrated example has a polarizing plate 10 and a retardation layer 20 laminated on the polarizing plate 10 via a first adhesive layer 31. A polarizing plate typically includes a polarizer and a protective layer arranged on at least one side of the polarizer. The polarizing plate 10 in the illustrated example includes a polarizer 11 and a first protective layer 12 arranged on one side of the polarizer 11 (the side opposite to the retardation layer). In the embodiment of the present invention, the retardation layer 20 is an alignment and solidification layer of a liquid crystal compound, and includes a permeation layer 20a formed by the adhesive of the first adhesive layer 31 permeating in the vicinity of the interface with the first adhesive layer 31. By providing such a permeation layer, peeling of the retardation layer (alignment and solidification layer of the liquid crystal compound) can be significantly suppressed. Furthermore, by directly providing the first adhesive layer 31 on the polarizer 11 as in this embodiment, peeling of the retardation layer (alignment and solidification layer of the liquid crystal compound) can be particularly significantly suppressed. According to the configuration of this embodiment, for example, the peel strength between the first adhesive layer and the alignment layer of the liquid crystal compound is extremely large, so that the first adhesive layer and the alignment layer of the liquid crystal compound do not peel off from each other in a normal peeling operation, and other interlayer peeling (for example, peeling between the polarizer and the first adhesive layer) can also be prevented.

[0011] FIG. 2 is a schematic cross-sectional view of a polarizing plate with a retardation layer according to another embodiment of the present invention. In the illustrated polarizing plate with a retardation layer 101, the polarizing plate 10 includes a polarizer 11, a first protective layer 12 arranged on one side of the polarizer 11 (opposite the retardation layer), and a second protective layer 13 arranged on the other side of the polarizer 11 (the retardation layer side). In this embodiment, the second protective layer 13 may include a permeation layer 13a formed by the permeation of the adhesive of the first adhesive layer 31 in the vicinity of the interface with the first adhesive layer 31. By providing the permeation layer 13a, for example, it is possible to prevent peeling between the first adhesive layer and the alignment solidified layer of the liquid crystal compound, and to increase the peel strength between the first adhesive layer and the second protective layer. Note that the permeation layer 13a is optional and may or may not be formed on the second protective layer 13.

[0012] The retardation layer 20 is an alignment solidified layer of a liquid crystal compound as described above. The retardation layer 20 may be a single layer of an alignment solidified layer as shown in FIG. 1 and FIG. 2, or may have a laminated structure of a first alignment solidified layer 21 and a second alignment solidified layer 22 as shown in FIG. 3. In the embodiment shown in FIG. 3, the first alignment solidified layer 21 and the second alignment solidified layer 22 are laminated via a second adhesive layer 32. In this case, the first alignment solidified layer 21 includes a permeation layer 21a formed by the adhesive of the second adhesive layer 32 permeating in the vicinity of the interface with the second adhesive layer 32; the second alignment solidified layer 22 includes a permeation layer 22a formed by the adhesive of the second adhesive layer 32 permeating in the vicinity of the interface with the second adhesive layer 32. In this embodiment, peeling between the second adhesive layer and the first alignment solidified layer 21 and the second alignment solidified layer 22 can be particularly significantly suppressed. For example, in a normal peeling operation, the second adhesive layer does not peel off from the first alignment solidified layer 21 and the second alignment solidified layer 22, and cohesive failure of the second adhesive layer may occur. In the embodiment of the present invention, it is sufficient that the adhesive of the first adhesive layer 31 penetrates into the retardation layer 20 and forms a permeation layer 20a (21a in the present embodiment) in the vicinity of the interface with the first adhesive layer 31. Therefore, the first alignment solidified layer 21 and the second alignment solidified layer 22 may be laminated, for example, via a pressure-sensitive adhesive layer.

[0013] As described above, the permeation layer is formed by the permeation of the adhesive of the adhesive layer. Specifically, the permeation layers 20a, 21a, and 22a are the portions of the alignment and solidification layers 20, 21, and 22 of the liquid crystal compound where the adhesive component exists, respectively; the permeation layer 13a is the portion of the second protective layer 13 where the adhesive component exists. Although the detailed structure of the permeation layer is not clear, it is presumed that the molecules of the permeated adhesive (substantially the cured component before curing) are entangled with the liquid crystal molecules of the alignment and solidification layer or the resin molecules constituting the second protective layer (in some cases, chemical bonds due to reaction) and thus peeling is suppressed. Furthermore, the formation of the permeation layer suppresses interface reflection, and as a result, display unevenness can be suppressed.

[0014] The thickness of the penetration layer is preferably 5 nm to 100 nm, more preferably 10 nm to 50 nm. The ratio of the thickness of the penetration layer to the thickness of the liquid crystal compound alignment solidified layer (penetration layer / alignment solidified layer) is preferably 0.2% to 20%, more preferably 0.2% to 10%. If the thickness of the penetration layer and the thickness ratio are within such ranges, peeling can be suppressed well, and display unevenness can be suppressed well. If the thickness of the penetration layer is too large, the penetration layer and / or the adhesive layer may become brittle and may be more likely to peel off. The thickness of the penetration layer can be measured from a transmission electron microscope (TEM) image of the cross section of the retardation layer-attached polarizing plate.

[0015] The peel strength between the first adhesive layer 31 and the alignment solidified layer 20 of the liquid crystal compound is preferably 0.7 N / 15 mm or more, more preferably 1.0 N / 15 mm or more, and even more preferably 1.5 N / 15 mm or more. It is difficult to specify the upper limit of the peel strength. This is because, before the first adhesive layer 31 and the alignment solidified layer 20 of the liquid crystal compound are peeled off, cohesive failure of the first adhesive layer or interlayer peeling between the first adhesive layer and the polarizing plate (typically, the second protective layer) occurs. The same is true for the peel strength between the second adhesive layer 32 and the first alignment solidified layer 21 and the second alignment solidified layer 22. The peel strength can be measured, for example, at a peel angle of 90° and a peel speed of 300 mm / min.

[0016] The above embodiments may be appropriately combined, and the components in the above embodiments may be modified as is obvious in the art. For example, the polarizing plate of the retardation layer-attached polarizing plate of Fig. 3 may be provided with a second protective layer as shown in Fig. 2; the retardation layer of the retardation layer-attached polarizing plate of Fig. 2 may have a laminated structure of a first alignment solidified layer 21 and a second alignment solidified layer 22 as shown in Fig. 3; the retardation layer of the retardation layer-attached polarizing plate of Fig. 1 to Fig. 3 may be replaced with an optically equivalent structure as long as it is an alignment solidified layer of a liquid crystal compound.

[0017] The retardation layer-attached polarizing plate according to the embodiment of the present invention may further include other optically functional layers. For example, the retardation layer-attached polarizing plate may further include another retardation layer and / or a conductive layer or a conductive layer-attached isotropic substrate (none are shown). The other retardation layer and the conductive layer or the conductive layer-attached isotropic substrate are typically provided on the outside of the retardation layer 20 (opposite side to the polarizing plate 10). The other retardation layer typically exhibits a relationship of nz>nx=ny in terms of refractive index characteristics. Such another retardation layer may be provided, for example, when the retardation layer 20 is a single layer of an orientation solidification layer. The other retardation layer and the conductive layer or the conductive layer-attached isotropic substrate are typically provided in this order from the retardation layer 20 side. The other retardation layer and the conductive layer or the conductive layer-attached isotropic substrate are typically any layers provided as necessary, and either one or both may be omitted. In addition, when a conductive layer or a conductive layer-attached isotropic substrate is provided, the retardation layer-attached polarizing plate can be applied to a so-called inner touch panel type input display device in which a touch sensor is incorporated between an image display cell (e.g., an organic EL cell) and a polarizing plate. The type, characteristics, number, combination, arrangement position, etc. of the optical functional layer that can be provided in the retardation layer-attached polarizing plate can be appropriately set according to the purpose.

[0018] The retardation layer-attached polarizing plate of the present invention may be in the form of a sheet or a long sheet. In this specification, the term "long sheet" means a long and narrow shape whose length is sufficiently long relative to its width, and includes, for example, a long and narrow shape whose length is 10 times or more, preferably 20 times or more, relative to its width. The long retardation layer-attached polarizing plate can typically be wound into a roll.

[0019] For practical purposes, a pressure-sensitive adhesive layer (not shown) is provided as the outermost layer on the side opposite to the polarizing plate of the retardation layer, so that the retardation layer-attached polarizing plate can be attached to an image display cell. Furthermore, it is preferable that a release film is temporarily attached to the surface of the pressure-sensitive adhesive layer until the retardation layer-attached polarizing plate is used. By temporarily attaching the release film, the pressure-sensitive adhesive layer is protected and the retardation layer-attached polarizing plate can be formed into a roll.

[0020] The total thickness of the retardation layer-attached polarizing plate is preferably 100 μm or less, more preferably 80 μm or less, further preferably 60 μm or less, and particularly preferably 55 μm or less. The lower limit of the total thickness may be, for example, 28 μm. According to the embodiment of the present invention, such an extremely thin retardation layer-attached polarizing plate can be realized. Such a retardation layer-attached polarizing plate can have extremely excellent flexibility and bending durability. Such a retardation layer-attached polarizing plate can be particularly suitably applied to a curved image display device and / or a bendable or foldable image display device. The total thickness of the retardation layer-attached polarizing plate refers to the sum of the thicknesses of all layers constituting the retardation layer-attached polarizing plate, excluding the adhesive layer.

[0021] The components of the retardation layer-attached polarizing plate will be described in more detail below.

[0022] B. Polarizing plate B-1.Polarizer Any appropriate polarizer can be adopted as the polarizer 11. For example, the resin film forming the polarizer may be a single-layer resin film or a laminate of two or more layers.

[0023] Specific examples of polarizers made of a single-layer resin film include hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formalized PVA films, and partially saponified ethylene-vinyl acetate copolymer films that have been dyed with iodine or a dichroic substance such as a dichroic dye and stretched, and polyene-based oriented films such as dehydrated PVA films and dehydrochlorinated polyvinyl chloride films. A polarizer obtained by dyeing a PVA film with iodine and uniaxially stretching it is preferably used because of its excellent optical properties.

[0024] The dyeing with iodine is carried out, for example, by immersing the PVA-based film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching may be carried out after the dyeing treatment, or may be carried out while dyeing. Alternatively, the film may be stretched and then dyed. If necessary, the PVA-based film may be subjected to a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like. For example, by immersing the PVA-based film in water and washing it with water before dyeing, it is possible to wash off dirt and antiblocking agents on the surface of the PVA-based film, and also to swell the PVA-based film and prevent uneven dyeing.

[0025] Specific examples of polarizers obtained using laminates include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate can be produced by, for example, applying a PVA-based resin solution to the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; stretching and dyeing the laminate to make the PVA-based resin layer a polarizer. In this embodiment, stretching typically includes immersing the laminate in an aqueous solution of boric acid to stretch it. Furthermore, stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95°C or higher) before stretching in the aqueous solution of boric acid. The obtained laminate of resin substrate / polarizer may be used as it is (i.e., the resin substrate may be used as a protective layer for the polarizer), or the resin substrate may be peeled off from the laminate of resin substrate / polarizer, and any suitable protective layer may be laminated on the peeled surface depending on the purpose. Details of such a method for producing a polarizer are described in, for example, JP2012-73580A. The entire disclosure of this publication is incorporated herein by reference.

[0026] The thickness of the polarizer is preferably 15 μm or less, more preferably 1 μm to 12 μm, further preferably 3 μm to 12 μm, and particularly preferably 3 μm to 8 μm. When the thickness of the polarizer is within this range, curling during heating can be well suppressed, and good appearance durability during heating can be obtained.

[0027] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is 43.0% to 46.0%, as described above, and preferably 44.5% to 46.0%. The degree of polarization of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more.

[0028] B-2.Protective layer The first protective layer 12 and the second protective layer 13 are each formed of any suitable film that can be used as a protective layer for a polarizer. Specific examples of materials that are the main components of the film include cellulose-based resins such as triacetyl cellulose (TAC), and transparent resins such as polyesters, polyvinyl alcohols, polycarbonates, polyamides, polyimides, polyethersulfones, polysulfones, polystyrenes, polynorbornenes, polyolefins, (meth)acrylics, and acetates. Other examples include thermosetting resins or ultraviolet-curing resins such as (meth)acrylics, urethanes, (meth)acrylic urethanes, epoxys, and silicones. Other examples include glassy polymers such as siloxane polymers. Polymer films described in JP 2001-343529 A (WO01 / 37007) can also be used. The material for this film may be, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain, and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain, such as a resin composition containing an alternating copolymer of isobutene and N-methylmaleimide, and an acrylonitrile-styrene copolymer. The polymer film may be, for example, an extrusion molded product of the above resin composition.

[0029] The retardation layer-attached polarizing plate according to the embodiment of the present invention is typically arranged on the viewing side of an image display device, as described later, and the first protective layer 12 is typically arranged on the viewing side. Therefore, the first protective layer 12 may be subjected to surface treatment such as hard coat treatment, anti-reflection treatment, anti-sticking treatment, and anti-glare treatment, as necessary. In addition, the first protective layer 12 may be subjected to treatment for improving visibility when viewed through polarized sunglasses (typically, imparting an (elliptical) polarization function or imparting an ultra-high phase difference) as necessary. By performing such treatment, excellent visibility can be achieved even when the display screen is viewed through polarized lenses such as polarized sunglasses. Therefore, the retardation layer-attached polarizing plate can be suitably applied to image display devices that can be used outdoors.

[0030] The thickness of the first protective layer is typically 300 μm or less, preferably 100 μm or less, more preferably 5 μm to 80 μm, and further preferably 10 μm to 60 μm. When a surface treatment is applied, the thickness of the outer protective layer includes the thickness of the surface treatment layer.

[0031] In one embodiment, the second protective layer 13 is preferably optically isotropic. In this specification, "optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm, and the retardation Rth(550) in the thickness direction is -10 nm to +10 nm. In one embodiment, the second protective layer 13 may be a retardation layer having any appropriate retardation value. In this case, the in-plane retardation Re(550) of the retardation layer is, for example, 110 nm to 150 nm. The thickness of the second protective layer is preferably 5 μm to 200 μm, more preferably 10 μm to 100 μm, and further preferably 10 μm to 60 μm.

[0032] C. Retardation layer As described above, the retardation layer 20 is an oriented and solidified layer of a liquid crystal compound. By using a liquid crystal compound, the difference between nx and ny of the obtained retardation layer can be significantly increased compared to non-liquid crystal materials, so that the thickness of the retardation layer for obtaining a desired in-plane retardation can be significantly reduced. As a result, a further reduction in thickness of the retardation layer-attached polarizing plate can be realized. In this embodiment, typically, rod-shaped liquid crystal compounds are oriented in a state aligned in the slow axis direction of the retardation layer (homogeneous orientation).

[0033] Examples of liquid crystal compounds include liquid crystal compounds whose liquid crystal phase is a nematic phase (nematic liquid crystals). Examples of such liquid crystal compounds include liquid crystal polymers and liquid crystal monomers. The mechanism by which liquid crystallinity of liquid crystal compounds is expressed may be either lyotropic or thermotropic. The liquid crystal polymers and liquid crystal monomers may be used alone or in combination.

[0034] When the liquid crystal compound is a liquid crystal monomer, the liquid crystal monomer is preferably a polymerizable monomer and a crosslinkable monomer. This is because the liquid crystal monomer can be polymerized or crosslinked (i.e., cured) to fix the alignment state of the liquid crystal monomer. After the liquid crystal monomer is aligned, for example, the liquid crystal monomers can be polymerized or crosslinked with each other to fix the alignment state. Here, a polymer is formed by polymerization, and a three-dimensional network structure is formed by crosslinking, but these are non-liquid crystals. Therefore, the formed retardation layer does not undergo transition to a liquid crystal phase, a glass phase, or a crystalline phase due to temperature changes specific to liquid crystal compounds, for example. As a result, the retardation layer becomes a retardation layer that is not affected by temperature changes and has extremely excellent stability.

[0035] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on the type of the liquid crystal monomer. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and most preferably 60°C to 90°C.

[0036] Any suitable liquid crystal monomer can be used as the liquid crystal monomer. For example, the polymerizable mesogen compounds described in JP-A-2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171, and GB2280445 can be used. Specific examples of such polymerizable mesogen compounds include BASF's product name LC242, Merck's product name E7, and Wacker-Chem's product name LC-Sillicon-CC3767. For example, nematic liquid crystal monomers are preferred as the liquid crystal monomer.

[0037] The alignment and solidification layer of the liquid crystal compound can be formed by performing an alignment treatment on the surface of a predetermined substrate, applying a coating liquid containing a liquid crystal compound to the surface to align the liquid crystal compound in a direction corresponding to the alignment treatment, and fixing the alignment state. In one embodiment, the substrate is any appropriate resin film, and the alignment and solidification layer formed on the substrate can be transferred to the surface of the polarizing plate 10. In another embodiment, the substrate can be the second protective layer 13. In this case, the transfer step is omitted, and lamination can be performed by roll-to-roll immediately after the formation of the alignment and solidification layer (retardation layer), further improving productivity.

[0038] As the above-mentioned alignment treatment, any suitable alignment treatment can be adopted. Specifically, mechanical alignment treatment, physical alignment treatment, and chemical alignment treatment can be mentioned. Specific examples of mechanical alignment treatment include rubbing treatment and stretching treatment. Specific examples of physical alignment treatment include magnetic field alignment treatment and electric field alignment treatment. Specific examples of chemical alignment treatment include oblique deposition method and photoalignment treatment. As the treatment conditions of various alignment treatments, any suitable conditions can be adopted according to the purpose.

[0039] The alignment of the liquid crystal compound is performed by treating it at a temperature at which the liquid crystal phase is exhibited according to the type of the liquid crystal compound. By performing such a temperature treatment, the liquid crystal compound assumes a liquid crystal state and aligns according to the alignment treatment direction on the surface of the substrate.

[0040] In one embodiment, the fixing of the alignment state is performed by cooling the liquid crystal compound aligned as described above. When the liquid crystal compound is a polymerizable monomer or a crosslinkable monomer, the fixing of the alignment state is performed by subjecting the liquid crystal compound aligned as described above to a polymerization treatment or a crosslinking treatment.

[0041] Specific examples of the liquid crystal compound and details of the method for forming the alignment fixing layer are described, for example, in Japanese Patent Application Laid-Open No. 2006-163343. The description of the said publication is incorporated herein by reference.

[0042] In one embodiment, as shown in FIGS. 1 and 2, the retardation layer 20 is a single layer of the alignment fixing layer of the liquid crystal compound. When the retardation layer 20 is composed of a single layer of the alignment fixing layer of the liquid crystal compound, its thickness is preferably 0.5 μm to 7 μm, more preferably 1 μm to 5 μm. By using the liquid crystal compound, an in-plane retardation equivalent to that of the resin film can be realized with a thickness much thinner than that of the resin film.

[0043] Typically, the retardation layer exhibits a refractive index characteristic relationship of nx > ny = nz. The retardation layer is typically provided to impart antireflection characteristics to the polarizing plate, and when the retardation layer is a single layer of the alignment fixing layer, it can function as a λ / 4 plate. In this case, the in-plane retardation Re(550) of the retardation layer is preferably 100 nm to 190 nm, more preferably 110 nm to 170 nm, and even more preferably 130 nm to 160 nm. Here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range not impairing the effects of the present invention, ny > nz or ny < nz may occur.

[0044] The Nz coefficient of the retardation layer is preferably 0.9 to 1.5, and more preferably 0.9 to 1.3. By satisfying such a relationship, when the obtained retardation layer-attached polarizing plate is used in an image display device, an extremely excellent reflection hue can be achieved.

[0045] The retardation layer may exhibit a reverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light, may exhibit a positive wavelength dispersion characteristic in which the retardation value decreases according to the wavelength of the measurement light, or may exhibit a flat wavelength dispersion characteristic in which the retardation value hardly changes according to the wavelength of the measurement light. In one embodiment, the retardation layer exhibits a reverse dispersion wavelength characteristic. In this case, Re(450) / Re(550) of the retardation layer is preferably 0.8 or more and less than 1, more preferably 0.8 or more and 0.95 or less. With such a configuration, it is possible to realize very excellent antireflection properties.

[0046] The angle θ between the slow axis of the retardation layer 20 and the absorption axis of the polarizer 11 is preferably 40° to 50°, more preferably 42° to 48°, and further preferably about 45°. If the angle θ is in such a range, by using a λ / 4 plate as the retardation layer as described above, a retardation layer-attached polarizing plate having very excellent circular polarization properties (resulting in very excellent antireflection properties) can be obtained.

[0047] In another embodiment, the retardation layer 20 may have a laminated structure of a first alignment solidified layer 21 and a second alignment solidified layer 22 as shown in FIG. 3. In this case, either the first alignment solidified layer 21 or the second alignment solidified layer 22 may function as a λ / 4 plate, and the other may function as a λ / 2 plate. Therefore, the thicknesses of the first alignment solidified layer 21 and the second alignment solidified layer 22 may be adjusted so as to obtain a desired in-plane retardation of a λ / 4 plate or a λ / 2 plate. For example, when the first alignment solidified layer 21 functions as a λ / 2 plate and the second alignment solidified layer 22 functions as a λ / 4 plate, the thickness of the first alignment solidified layer 21 is, for example, 2.0 μm to 3.0 μm, and the thickness of the second alignment solidified layer 22 is, for example, 1.0 μm to 2.0 μm. In this case, the in-plane retardation Re(550) of the first alignment solidified layer is preferably 200 nm to 300 nm, more preferably 230 nm to 290 nm, and even more preferably 250 nm to 280 nm. The in-plane retardation Re(550) of the second alignment solidified layer is as described above for the single-layer alignment solidified layer. The angle between the slow axis of the first alignment solidified layer and the absorption axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and even more preferably about 15°. The angle between the slow axis of the second alignment solidified layer and the absorption axis of the polarizer is preferably 70° to 80°, more preferably 72° to 78°, and even more preferably about 75°. With this configuration, it is possible to obtain characteristics close to ideal reverse wavelength dispersion characteristics, and as a result, it is possible to realize very excellent antireflection characteristics. The liquid crystal compounds constituting the first alignment solidified layer and the second alignment solidified layer, the methods for forming the first alignment solidified layer and the second alignment solidified layer, the optical characteristics, etc. are as described above for the single alignment solidified layer.

[0048] D.Adhesive layer The first adhesive layer and the second adhesive layer are collectively described as an adhesive layer. The first adhesive layer and the second adhesive layer may have the same configuration, or may have different configurations. Any suitable adhesive that can penetrate into the alignment solidified layer of the liquid crystal compound to form a permeation layer can be adopted as the adhesive constituting the adhesive layer. Representative examples of the adhesive include active energy ray curable adhesives. Examples of the active energy ray curable adhesives include ultraviolet ray curable adhesives and electron beam curable adhesives. In addition, from the viewpoint of the curing mechanism, examples of the active energy ray curable adhesives include radical curable adhesives, cationic curable adhesives, anionic curable adhesives, and hybrids of radical curable adhesives and cationic curable adhesives. Representative examples of the radical curable ultraviolet ray curable adhesives can be used. This is because they are highly versatile and the properties (configuration) can be easily adjusted.

[0049] The adhesive typically contains a curing component and a photopolymerization initiator. Typical examples of the curing component include monomers and / or oligomers having functional groups such as (meth)acrylate groups and (meth)acrylamide groups. Specific examples of the curing component include tripropylene glycol diacrylate, 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, phenoxydiethylene glycol acrylate, cyclic trimethylolpropane formal acrylate, dioxane glycol diacrylate, EO-modified diglycerin tetraacrylate, γ-butyrolactone acrylate, acryloylmorpholine, unsaturated fatty acid hydroxyalkyl ester-modified ε-caprolactone, N-methylpyrrolidone, hydroxyethylacrylamide, N-methylolacrylamide, N-methoxymethylacrylamide, and N-ethoxymethylacrylamide. These curing components may be used alone or in combination of two or more.

[0050] Preferably, the adhesive contains a curing component having a heterocycle. Examples of the curing component having a heterocycle include acryloylmorpholine, γ-butyrolactone acrylate, unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone, and N-methylpyrrolidone. More preferred curing components are unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone and acryloylmorpholine, and particularly preferred curing components are acryloylmorpholine. The curing component having a heterocycle may be contained in the adhesive at a ratio of preferably 50 parts by weight or more, more preferably 60 parts by weight or more, and even more preferably 70 to 95 parts by weight, relative to 100 parts by weight of the curing component (the total of the curing component and the oligomer component when an oligomer component is present, as described below). The acryloylmorpholine may be contained in the adhesive at a ratio of preferably 5 to 60 parts by weight, more preferably 10 to 50 parts by weight, relative to 100 parts by weight of the curing component (the total of the curing component and the oligomer component when an oligomer component is present).

[0051] The adhesive may further contain an oligomer component in addition to the above-mentioned curing component. By using the oligomer component, the viscosity of the adhesive before curing can be reduced and the operability can be improved. A representative example of the oligomer component is a (meth)acrylic oligomer. Examples of (meth)acrylic monomers constituting the (meth)acrylic oligomer include (meth)acrylic acid (carbon number 1 to 20) alkyl esters, cycloalkyl (meth)acrylates (e.g., cyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate, etc.), aralkyl (meth)acrylates (e.g., benzyl (meth)acrylate, etc.), polycyclic (meth)acrylates (e.g., 2-isobornyl (meth)acrylate, 2-norbornylmethyl (meth)acrylate, 5-norbornen-2-yl-methyl (meth)acrylate, 3-methyl-2-norbornylmethyl (meth)acrylate, etc.), hydroxyl group-containing (meth)acrylic acid esters (e.g., hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2,3-dihydroxypropylmethyl-butyl (meth)methacrylate, etc.), alkoxy group- or phenoxy group-containing (meth)acrylic acid esters (e.g., hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2,3-dihydroxypropylmethyl-butyl (meth)methacrylate, etc.), and the like. ) acrylic acid esters (2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-methoxymethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, ethyl carbitol (meth)acrylate, phenoxyethyl (meth)acrylate, etc.), epoxy group-containing (meth)acrylic acid esters (for example, glycidyl (meth)acrylate, etc.), halogen-containing (meth)acrylic acid esters (for example, 2,2,2-trifluoroethyl (meth)acrylate, 2,2,2-trifluoroethylethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropentyl (meth)acrylate, heptadecafluorodecyl (meth)acrylate, etc.), alkylaminoalkyl (meth)acrylates (for example, dimethylaminoethyl (meth)acrylate, etc.).Specific examples of (meth)acrylic acid (C1 to C20) alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, 2-methyl-2-nitropropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, n-pentyl (meth)acrylate, t-pentyl (meth)acrylate, 3-pentyl (meth)acrylate, 2,2-dimethylbutyl (meth)acrylate, n-hexyl (meth)acrylate, cetyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 4-methyl-2-propylpentyl (meth)acrylate, and n-octadecyl (meth)acrylate. These (meth)acrylates may be used alone or in combination of two or more kinds.

[0052] As the photopolymerization initiator, a photopolymerization initiator well known in the art can be used in an amount well known in the art, and therefore detailed description thereof will be omitted.

[0053] The thickness of the adhesive layer (after the adhesive is cured) is preferably 0.1 μm to 3.0 μm. By applying the adhesive to such a thickness, a permeation layer of appropriate thickness can be formed.

[0054] Details of the adhesive are described in, for example, JP 2018-017996 A. The disclosure of this publication is incorporated herein by reference.

[0055] E. Another retardation layer The separate retardation layer may be a so-called positive C plate whose refractive index characteristic shows the relationship nz>nx=ny, as described above. By using a positive C plate as the separate retardation layer, it is possible to effectively prevent reflection in an oblique direction, and the anti-reflection function can be made to have a wide viewing angle. In this case, the thickness direction retardation Rth(550) of the separate retardation layer is preferably -50 nm to -300 nm, more preferably -70 nm to -250 nm, further preferably -90 nm to -200 nm, and particularly preferably -100 nm to -180 nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. That is, the in-plane retardation Re(550) of the separate retardation layer may be less than 10 nm.

[0056] The other retardation layer having a refractive index characteristic of nz>nx=ny may be formed of any appropriate material. The other retardation layer is preferably made of a film containing a liquid crystal material fixed in a homeotropic alignment. The liquid crystal material (liquid crystal compound) that can be homeotropically aligned may be a liquid crystal monomer or a liquid crystal polymer. Specific examples of the liquid crystal compound and the method of forming the retardation layer include the liquid crystal compound and the method of forming the retardation layer described in

[0020] to

[0028] of JP-A-2002-333642. In this case, the thickness of the other retardation layer is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and even more preferably 0.5 μm to 5 μm.

[0057] F. Conductive layer or isotropic substrate with conductive layer The conductive layer can be formed by forming a metal oxide film on any suitable substrate by any suitable film forming method (e.g., vacuum deposition, sputtering, CVD, ion plating, spraying, etc.). Examples of metal oxides include indium oxide, tin oxide, zinc oxide, indium-tin composite oxide, tin-antimony composite oxide, zinc-aluminum composite oxide, and indium-zinc composite oxide. Among these, indium-tin composite oxide (ITO) is preferred.

[0058] When the conductive layer contains a metal oxide, the thickness of the conductive layer is preferably 50 nm or less, more preferably 35 nm or less. The lower limit of the thickness of the conductive layer is preferably 10 nm.

[0059] The conductive layer may be transferred from the substrate to the retardation layer (or another retardation layer, if present) and used alone as a constituent layer of the retardation layer-attached polarizing plate, or may be laminated with the substrate (substrate with conductive layer) to the retardation layer (or another retardation layer, if present). Preferably, the substrate is optically isotropic, and therefore the conductive layer can be used as an isotropic substrate with a retardation layer in the retardation layer-attached polarizing plate.

[0060] Any suitable isotropic substrate may be adopted as the optically isotropic substrate (isotropic substrate). Examples of materials constituting the isotropic substrate include materials having a resin without a conjugated system, such as norbornene-based resins and olefin-based resins, as the main skeleton, and materials having a ring structure, such as a lactone ring or a glutarimide ring, in the main chain of an acrylic resin. When such materials are used, the occurrence of retardation due to the orientation of molecular chains can be suppressed to a small value when the isotropic substrate is formed. The thickness of the isotropic substrate is preferably 50 μm or less, more preferably 35 μm or less. The lower limit of the thickness of the isotropic substrate is, for example, 20 μm.

[0061] The conductive layer and / or the conductive layer of the isotropic substrate with a conductive layer may be patterned as necessary. By patterning, a conductive portion and an insulating portion may be formed. As a result, an electrode may be formed. The electrode may function as a touch sensor electrode that senses contact with the touch panel. Any appropriate method may be adopted as the patterning method. Specific examples of the patterning method include a wet etching method and a screen printing method.

[0062] G. Image display device The retardation layer-attached polarizing plate described in the above items A to F can be applied to an image display device. Therefore, the present invention includes an image display device using such a retardation layer-attached polarizing plate. Representative examples of image display devices include liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices, inorganic EL display devices (e.g., quantum dot display devices)). An image display device according to an embodiment of the present invention includes the retardation layer-attached polarizing plate described in the above items A to F on the viewing side. The retardation layer-attached polarizing plate is laminated so that the retardation layer is on the image display cell (e.g., liquid crystal cell, organic EL cell, inorganic EL cell) side (so that the polarizer is on the viewing side). In one embodiment, the image display device has a curved shape (substantially a curved display screen) and / or can be bent or folded. In such an image display device, the effect of the retardation layer-attached polarizing plate of the present invention becomes remarkable. EXAMPLES

[0063] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring each property are as follows. In the examples and comparative examples, "parts" and "%" are by weight unless otherwise specified.

[0064] [Production Example 1] Adhesive A was prepared by mixing 50 parts of unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone (Daicel Corporation's "Placcel FA1DDM"), 40 parts of acryloylmorpholine (Kojinsha's "ACMO (registered trademark)"), 10 parts of acrylic oligomer (Toagosei Co., Ltd.'s "ARFON UP-1190"), and 3 parts of "KAYACURE DETX-S" (Nippon Kayaku Co., Ltd.) and 3 parts of OMNIRAD907 (IGM Resins Italia Srl) as photopolymerization initiators.

[0065] [Production Example 2] Adhesive B was prepared by mixing 50 parts of unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone (Daicel Corporation's "Placcel FA1DDM"), 40 parts of phenoxydiethylene glycol acrylate (Kyoeisha Chemical's "Light Acrylate P2H-A"), 10 parts of acrylic oligomer (Toagosei Co., Ltd.'s "ARFON UP-1190"), and 3 parts of "KAYACURE DETX-S" (Nippon Kayaku Co., Ltd.) and 3 parts of OMNIRAD907 (IGM Resins Italia Srl) as photopolymerization initiators.

[0066] [Example 1] 1. Preparation of Polarizing Plates A-PET (amorphous polyethylene terephthalate) film (manufactured by Mitsubishi Plastics, Inc., trade name: Novaclear SH046, thickness 200 μm) was prepared as a substrate, and the surface was subjected to corona treatment (58 W / m2 / min). On the other hand, PVA (polymerization degree 4200, saponification degree 99.2%) to which 1 wt% of acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name: Gohsefimer Z200, polymerization degree 1200, saponification degree 99.0% or more, acetoacetyl-modification degree 4.6%) was added was prepared, and coated so that the film thickness after drying was 12 μm, and dried by hot air drying for 10 minutes in an atmosphere of 60 ° C. to prepare a laminate having a PVA-based resin layer on the substrate. Next, this laminate was first stretched 2.0 times in air at 130 ° C. to obtain a stretched laminate. Next, the stretched laminate was immersed in a boric acid insolubilizing aqueous solution having a liquid temperature of 30° C. for 30 seconds to insolubilize the PVA-based resin layer in which the PVA molecules contained in the stretched laminate were oriented. The boric acid insolubilizing aqueous solution in this step had a boric acid content of 3% by weight relative to 100% by weight of water. The stretched laminate was dyed to produce a colored laminate. The colored laminate was obtained by immersing the stretched laminate in a dyeing solution containing iodine and potassium iodide at a liquid temperature of 30° C., thereby adsorbing iodine to the PVA-based resin layer contained in the stretched laminate. The iodine concentration and the immersion time were adjusted so that the single transmittance of the obtained polarizer was 44.5%. Specifically, the dyeing solution was a solution containing water as a solvent, with an iodine concentration in the range of 0.08 to 0.25% by weight and a potassium iodide concentration in the range of 0.56 to 1.75% by weight. The concentration ratio of iodine to potassium iodide was 1:7. Next, the colored laminate was immersed in a 30°C boric acid crosslinking aqueous solution for 60 seconds to crosslink the PVA molecules of the iodine-adsorbed PVA-based resin layer. The boric acid crosslinking aqueous solution in this step had a boric acid content of 3% by weight relative to 100% by weight of water, and a potassium iodide content of 3% by weight relative to 100% by weight of water. The obtained colored laminate was then stretched 2.7 times in the same direction as the above-mentioned stretching in air at a stretching temperature of 70°C in the boric acid aqueous solution, and the final stretching ratio was 5.4 times to obtain a laminate of a substrate / polarizer. The polarizer had a thickness of 5 μm.The boric acid crosslinking aqueous solution in this step had a boric acid content of 6.5% by weight relative to 100% by weight of water, and a potassium iodide content of 5% by weight relative to 100% by weight of water. The obtained laminate was taken out of the boric acid aqueous solution, and the boric acid attached to the surface of the polarizer was washed with an aqueous solution containing 2% by weight of potassium iodide relative to 100% by weight of water. The washed laminate was dried with hot air at 60°C. A 40 μm-thick triacetyl cellulose (TAC) film was attached to the polarizer surface of the substrate / polarizer laminate obtained above via a PVA-based adhesive to obtain a laminate having a configuration of protective layer (TAC film) / polarizer / resin substrate. Furthermore, the resin substrate was peeled off from this laminate, and a 40 μm-thick TAC film was attached to the peeled surface to obtain a laminate (polarizing plate) having a configuration of protective layer (TAC film) / polarizer / protective layer (TAC film).

[0067] 2. Preparation of a layer of liquid crystal molecules that form the retardation layer A liquid crystal composition (coating liquid) was prepared by dissolving 10 g of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF: product name "Paliocolor LC242", represented by the following formula) and 3 g of a photopolymerization initiator for the polymerizable liquid crystal compound (manufactured by BASF: product name "Irgacure 907") in 40 g of toluene. [ka] The surface of a polyethylene terephthalate (PET) film (thickness 38 μm) was rubbed with a rubbing cloth to perform an alignment treatment. The direction of the alignment treatment was set to be 45° from the viewing side with respect to the direction of the absorption axis of the polarizer when it was attached to the polarizing plate. The above liquid crystal coating liquid was applied to this alignment-treated surface with a bar coater, and the liquid crystal compound was aligned by heating and drying at 90° C. for 2 minutes. The liquid crystal layer thus formed was then irradiated with 1 mJ / cm 2 using a metal halide lamp. 2The liquid crystal layer was cured by irradiating the liquid crystal with light, thereby forming a liquid crystal alignment solidified layer A on the PET film. The liquid crystal alignment solidified layer A had a thickness of 1.5 μm and an in-plane retardation Re(550) of 140 nm. Furthermore, the liquid crystal alignment solidified layer A had a refractive index distribution of nx>ny=nz.

[0068] 3. Preparation of polarizing plate with retardation layer The liquid crystal alignment solidified layer A obtained in 2 above was transferred to the surface of the polarizing plate obtained in 1 above (substantially, the TAC film as a protective layer) via the adhesive A obtained in Production Example 1 (thickness after curing: 1.0 μm). In this way, a retardation layer-attached polarizing plate having a configuration of protective layer (TAC film) / polarizer / protective layer (TAC film) / adhesive layer (adhesive A) / retardation layer (liquid crystal alignment solidified layer A, λ / 4 plate, slow axis 45° direction) was obtained. When the cross section of the obtained retardation layer-attached polarizing plate was observed with a transmission electron microscope (TEM), a permeation layer formed by the adhesive A permeating both the retardation layer (liquid crystal alignment solidified layer A) and the protective layer (TAC film) was confirmed. A TEM image showing the state of the interface between the adhesive layer and the retardation layer (liquid crystal alignment solidified layer A) is shown in FIG. 4.

[0069] 4. Evaluation of peelability The obtained polarizing plate with a retardation layer was evaluated for peelability. Specifically, the evaluation is as follows. The obtained polarizing plate with a retardation layer was cut into a size of 200 mm parallel to the absorption axis direction of the polarizer and 15 mm in the perpendicular direction, and was attached to a glass plate. A peel test was performed in the 90° direction at a peel speed of 300 mm / min using a Tensilon universal testing machine RTC manufactured by A&D Co., Ltd., and the peel strength at that time was measured. In the peel test, peeling occurred at the interface between the TAC film and the adhesive layer, and the peel strength was 0.8 N / 15 mm.

[0070] [Example 2] A polarizing plate with a retardation layer having a structure of protective layer (TAC film) / polarizer / protective layer (COP film) / adhesive layer (adhesive A) / retardation layer (liquid crystal alignment solidified layer A, λ / 4 plate, slow axis 45° direction) was obtained in the same manner as in Example 1, except that a cycloolefin resin (COP) film was attached to the release surface of the resin substrate instead of a TAC film in the production of the polarizing plate. When the cross section of the obtained polarizing plate with a retardation layer was observed with a transmission electron microscope (TEM), a permeation layer formed by the adhesive A permeating into the retardation layer (liquid crystal alignment solidified layer A) was confirmed. Furthermore, the peelability of the obtained polarizing plate with a retardation layer was evaluated in the same manner as in Example 1. In the peel test, peeling occurred at the interface between the retardation layer (liquid crystal alignment solidified layer A) and the adhesive layer, and the peel strength was 0.7 N / 15 mm.

[0071] [Example 3] A polarizing plate with a retardation layer having a structure of protective layer (TAC film) / polarizer / protective layer (acrylic film) / adhesive layer (adhesive A) / retardation layer (liquid crystal alignment solidified layer A, λ / 4 plate, slow axis 45° direction) was obtained in the same manner as in Example 1, except that an acrylic resin film was attached to the release surface of the resin substrate instead of the TAC film in the production of the polarizing plate. When the cross section of the obtained polarizing plate with a retardation layer was observed with a transmission electron microscope (TEM), a permeation layer formed by the adhesive A permeating into the retardation layer (liquid crystal alignment solidified layer A) was confirmed. Furthermore, the peelability of the obtained polarizing plate with a retardation layer was evaluated in the same manner as in Example 1. In the peel test, peeling occurred at the interface between the acrylic film and the adhesive layer, and the peel strength was 0.3 N / 15 mm.

[0072] [Example 4] A polarizing plate with a retardation layer having a structure of protective layer (TAC film) / polarizer / adhesive layer (adhesive A) / retardation layer (liquid crystal alignment solidified layer A, λ / 4 plate, slow axis 45° direction) was obtained in the same manner as in Example 1, except that a protective layer was not provided on the peelable surface of the resin substrate in the production of the polarizing plate. When the cross section of the obtained polarizing plate with a retardation layer was observed with a transmission electron microscope (TEM), a permeation layer formed by the adhesive A permeating into the retardation layer (liquid crystal alignment solidified layer A) was confirmed. Furthermore, the peelability of the obtained polarizing plate with a retardation layer was evaluated in the same manner as in Example 1. In the peel test, no peeling occurred.

[0073] [Example 5] A polarizing plate having a protective layer (TAC film) / polarizer structure was obtained in the same manner as in Example 4. A liquid crystal alignment solidified layer B was formed on a PET film in the same manner as in Example 1, except that the coating thickness was changed and the orientation treatment direction was set to a 15° direction from the viewing side relative to the absorption axis direction of the polarizer. The liquid crystal alignment solidified layer B had a thickness of 2.5 μm and an in-plane retardation Re (550) of 270 nm. The liquid crystal alignment solidified layer B was transferred to the polarizer surface of the polarizing plate via adhesive A (thickness after curing: 1.0 μm), and further, the liquid crystal alignment solidified layer A prepared in the same manner as in Example 1, except that the orientation treatment direction was set to a 75° direction from the viewing side relative to the absorption axis direction of the polarizer, was transferred to the surface of the liquid crystal alignment solidified layer B via adhesive A (thickness after curing: 1.0 μm). In this way, a retardation layer-attached polarizing plate having a structure of protective layer (TAC film) / polarizer / adhesive layer (adhesive A) / liquid crystal alignment solidified layer B (lambda / 2 plate, slow axis 15° direction) / adhesive layer (adhesive A) / liquid crystal alignment solidified layer A (lambda / 4 plate, slow axis 75° direction) was obtained. When the cross section of the obtained retardation layer-attached polarizing plate was observed with a transmission electron microscope (TEM), a permeation layer formed by the adhesive A permeating both the liquid crystal alignment solidified layer A and the liquid crystal alignment solidified layer B was confirmed. Furthermore, the peelability of the obtained retardation layer-attached polarizing plate was evaluated in the same manner as in Example 1. In the peel test, the adhesive layer between the liquid crystal alignment solidified layer A and the liquid crystal alignment solidified layer B was cohesively broken.

[0074] [Comparative Example 1] A polarizing plate with a retardation layer having a structure of protective layer (TAC film) / polarizer / adhesive layer (adhesive B) / retardation layer (liquid crystal alignment solidified layer A, λ / 4 plate, slow axis 45° direction) was obtained in the same manner as in Example 4, except that adhesive B (thickness after curing: 1.0 μm) obtained in Production Example 2 was used instead of adhesive A. When the cross section of the obtained polarizing plate with a retardation layer was observed with a transmission electron microscope (TEM), no permeation layer was confirmed. A TEM image showing the state of the interface between the adhesive layer and the retardation layer (liquid crystal alignment solidified layer A) is shown in FIG. 5. Furthermore, the peelability of the obtained polarizing plate with a retardation layer was evaluated in the same manner as in Example 1. In the peel test, peeling occurred at the interface between the liquid crystal alignment solidified layer A and the adhesive layer, and the peel strength was 0.5 N / 15 mm.

[0075] [evaluation] As is clear from a comparison between the Examples and the Comparative Examples, the Examples of the present invention can suppress peeling of the liquid crystal alignment solidified layer. [Industrial Applicability]

[0076] The retardation layer-attached polarizing plate of the present invention is suitably used as a circular polarizing plate for liquid crystal displays, organic EL displays, and inorganic EL displays. [Explanation of symbols]

[0077] 10 Polarizing plate 11 Polarizer 12 First protective layer 13 Second layer of protection 20 Retardation layer 20a Permeation layer 21 First orientation solidification layer 21a Penetration layer 22 Second alignment solidification layer 22a Penetration layer 31 First adhesive layer 32 Second adhesive layer 100 Polarizing plate with retardation layer 101 Polarizing plate with retardation layer 102 Polarizing plate with retardation layer

Claims

1. A polarizing plate including a polarizer and protective layers disposed on both sides of the polarizer, and a retardation layer laminated on the polarizing plate via a first adhesive layer. the retardation layer is an alignment solidified layer of a liquid crystal compound, and includes a permeation layer formed by permeating an adhesive of the first adhesive layer into the vicinity of an interface between the retardation layer and the first adhesive layer, a protective layer disposed on the retardation layer side of the polarizer includes a permeation layer formed by permeation of an adhesive of the first adhesive layer into the protective layer in the vicinity of an interface between the protective layer and the first adhesive layer, the thickness of the penetration layer formed in the vicinity of the interface between the retardation layer and the first adhesive layer and the thickness of the penetration layer formed in the vicinity of the interface between the protective layer and the first adhesive layer are each 5 nm to 100 nm; the peel strength between the protective layer and the first adhesive layer is 0.3 N / 15 mm to 0.8 N / 15 mm; The peel strength between the retardation layer and the first adhesive layer is 1.5 N / 15 mm or more, a protective layer disposed on the retardation layer side of the polarizer is composed of a cellulose-based resin film or a (meth)acrylic resin film, the retardation layer is a single layer of a liquid crystal compound aligned and fixed, The retardation layer has an Re(550) of 100 nm to 190 nm, the angle between the slow axis of the retardation layer and the absorption axis of the polarizer is 40° to 50°; Polarizing plate with retardation layer.

2. A polarizing plate including a polarizer and protective layers arranged on both sides of the polarizer, and a retardation layer laminated on the polarizing plate via a first adhesive layer. the retardation layer is an alignment solidified layer of a liquid crystal compound, and includes a permeation layer formed by permeating an adhesive of the first adhesive layer into the vicinity of an interface between the retardation layer and the first adhesive layer, a protective layer disposed on the retardation layer side of the polarizer includes a permeation layer formed by permeation of an adhesive of the first adhesive layer into the protective layer in the vicinity of an interface between the protective layer and the first adhesive layer, the thickness of the penetration layer formed in the vicinity of the interface between the retardation layer and the first adhesive layer and the thickness of the penetration layer formed in the vicinity of the interface between the protective layer and the first adhesive layer are each 5 nm to 100 nm; the peel strength between the protective layer and the first adhesive layer is 0.3 N / 15 mm to 0.8 N / 15 mm; The peel strength between the retardation layer and the first adhesive layer is 1.5 N / 15 mm or more, a protective layer disposed on the retardation layer side of the polarizer is composed of a cellulose-based resin film or a (meth)acrylic resin film, the retardation layer has a first alignment / solidified layer of a liquid crystal compound, and a second alignment / solidified layer of a liquid crystal compound laminated on the first alignment / solidified layer of a liquid crystal compound via a second adhesive layer; the alignment and solidified layer of the first liquid crystal compound and the alignment and solidified layer of the second liquid crystal compound each include a permeation layer formed by permeation of an adhesive of the second adhesive layer in the vicinity of an interface between the alignment and solidified layer of the first liquid crystal compound and the alignment and solidified layer of the second liquid crystal compound and the second adhesive layer, The Re(550) of the alignment solidified layer of the first liquid crystal compound is 200 nm to 300 nm, and the angle between the slow axis and the absorption axis of the polarizer is 10° to 20°, the Re(550) of the alignment solidified layer of the second liquid crystal compound is 100 nm to 190 nm, and the angle between the slow axis of the layer and the absorption axis of the polarizer is 70° to 80°; Polarizing plate with retardation layer.

3. 3. The retardation layer-attached polarizing plate according to claim 2, wherein the adhesive of each of the first and second adhesive layers contains acryloylmorpholine.

4. 4. The polarizing plate with a retardation layer according to claim 1, further comprising another retardation layer on the outer side of the retardation layer, the refractive index characteristics of the other retardation layer exhibiting a relationship of nz>nx=ny.

5. An image display device comprising the retardation layer-attached polarizing plate according to claim 1 .

Citation Information

Patent Citations

  • Card reader

    JP1982045686A

  • Method for manufacturing laminate, laminate, polarizing plate and image display device

    JP2016133728A

  • Optical layered product

    JP2016186558A

  • Polarizing plate having retardation layer and picture display unit

    JP2017054093A